The relationship between mindfulness and second language resilience among Chinese English majors: the mediating role of academic hope - Yanping Rui; Yanjuan Zhang; Huiyi Jin (BMC Psychology)
Abstract Background In light of the heightened expectations surrounding the development of foreign language professionals in the age of artificial intelligence and the pursuit of academic excellence in Asian culture, Chinese English majors are faced with tremendous academic pressure. Accordingly, as a positive individual trait, second language (L2) resilience has recently received considerable attention in foreign and second language learning research. Purpose Based on the hope theory, the broaden-and-build theory, and resilience theory framework, the present study explores the influence of mindfulness and academic hope on Chinese English majors’ L2 resilience. Methods We employed descriptive statistics, correlation analysis, and structural equation modeling (SEM) to investigate the relationships among mindfulness, academic hope, and L2 resilience within 351 Chinese English majors. Results The study results found that Chinese English majors’ mindfulness positively predicted students’ academic hope and L2 resilience. Their academic hope also had a significant correlation with L2 resilience. Finally, SEM showed that academic hope remarkably mediated the relationship between mindfulness and L2 resilience. Conclusions In a word, this paper reveals the important role of mindfulness and academic hope in enhancing students’ L2 resilience. Besides, strengthening Chinese English majors’ mindfulness also can promote their academic hope. At this point, it also underscores the essential mediating role of academic hope between mindfulness and L2 resilience. Implications The results of this study have implications for fostering students’ L2 resilience and helping them cope with the challenge of the language learning process. Teachers can implement relevant intervention promoting students’ mindfulness, academic hope, and L2 resilience into language instruction, which conducing to students’ language learning success.